Challenges and Potential of a Collaborative Approach to Education Reform - Bodilly, Susan J. (RAND Corporation, 2004)
The Ford Foundation developed the Collaborating for Education Reform Initiative, providing grants to collaboratives in urban settings to improve the quality of teaching. Eight sites signed on, and the RAND Corporation assessed their progress. The authors found that, while none had met final goals, the collaboratives had varying degrees of success and some offered promise. By adopting such techniques as clear communication of expectations and involvement of school staff, collaboratives stand a better chance of success.